A novel dengue virus serotype-2 nanovaccine induces robust humoral and cell-mediated immunity in mice. Issue 14 (30th March 2015) - Hunsawong, Taweewun; Sunintaboon, Panya; Warit, Saradee; Thaisomboonsuk, Butsaya; Jarman, Richard G.; Yoon, In-Kyu; Ubol, Sukathida; Fernandez, Stefan
Abstract: Dengue virus (DENV), a member of the Flaviviridae family, can be transmitted to humans through the bite of infected Aedes mosquitoes. The incidence of dengue has increased worldwide over the past few decades. Inadequate vector control, changing global ecology, increased urbanization, and faster global travel are factors enhancing the rapid spread of the virus and its vector. In the absence of specific antiviral treatments, the search for a safe and effective vaccine grows more imperative. Many strategies have been utilized to develop dengue vaccines. Here, we demonstrate the immunogenic properties of a novel dengue nanovaccine (DNV), composed of ultraviolet radiation (UV)-inactivated DENV-2, which has been loaded into the nanoparticles containing chitosan/ Mycobacterium bovis Bacillus Calmette-Guerin cell wall components (CS/BCG-NPs). We investigated the immunogenicity of DNV in a Swiss albino mouse model. Inoculation with various concentrations of vaccine (0.3, 1, 3 and 10 μg/dose) with three doses, 15-day apart, induced strong anti-dengue IgM and IgG antibodies in the mouse serum along with neutralizing antibody against DENV-2 reference strain (16681), a clinical-isolate strain (00745/10) and the mouse-adapted New Guinea-C (NGC) strain. Cytokine and chemokine secretion in the serum of DNV-immunized mice showed elevated levels of IFN-γ, IL-2, IL-5, IL-12p40, IL-12p70, IL-17, eotaxin and RANTES, all of which have varying immune functions. Furthermore, we observed a DNV dose-dependent increase in the frequencies of IFN-γ-producing CD4 + and CD8 + T cells after in vitro stimulation of nucleated cells. Based on these findings, DNV has the potential to become a candidate dengue vaccine.